Towards a theory for professional communications. Discourse and communication elements in contemporary marketing and pr strategies. - Haase, Fee-alexandra (Nómadas. Critical Journal of Social and Juridical Sciences, 2009)
This article examines elements of discourse in professional communication using examples of marketing, PR, and advertising focusing on the communicative functions that serve the major aims of each of the professional communication fields we define as values. It follows the rhetorical definition of communication as a persuasive figure of speech and demonstrates this impact in examples. This professional mass media communication in marketing, PR, and advertising serves commercial interests. It aims to incorporate the audience into the flow of discourses that is set up for serving the commercial interests.